Could Virtual Reality Make us More Human? - Riecke, Bernhard E. (TEDxEastVan, 2017)
How we could use the potential of virtual reality to go beyond entertainment and gaming, for creating positive or even transformational experiences we might otherwise not be able to have? And how could we democratize the medium and put this powerful technology into the creative hands of more people? Virtual reality is becoming increasingly powerful and accessible, and offers the unique opportunity to provide first-hand interactive and embodied experiences. Bernhard paints a vision of how we could use this potential for empowering people to create positive experiences worth spreading.
Keywords: EarthGazement; Riecke; Riecke_2017; earthgazing; talkWithoutPaper